FAKTOR-FAKTOR YANG MEMPENGARUHI KONSUMEN TERHADAP PEMBELIAN BERAS ORGANIK (Studi kasus di Kecamatan Selopuro Kabupaten Blitar) - Zamrodah, Yuhanin (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2021)
The purpose of this study was to determine the characteristics of consumers of organic rice and to identify the factors that influence consumers to purchase organic rice in Selopuro District. The implementation of this research activity will be carried out in April 2021 - June 2021 in Selopuro District, Blitar Regency. The data analysis method used in this research is descriptive analysis and multiple linear regression analysis. The independent variables in this study include the price of organic rice, the price of non-organic rice, income, education, employment status, consumer tastes, consumer lifestyle, health and access to buy organic rice. While the dependent variable in this study is the number of consumer demand for organic rice. The results of data analysis found that the X2 (non-organic rice) variable was 0.042, X4 (Education) was 0.054, X7 (lifestyle) was 0.042 and X8 (health) was 0.038 very influential on the purchase of organic rice. The results of the t test show that some variables have positive numbers and some variables have negative numbers, while the F test simultaneously shows that the calculated F value is 2,951 which is greater than the F table of 2,420. This indicates that the independent variables have a significant influence on purchasing decisions.